Union Activity and Dual Loyalty - St-Laurent, Jacques (Relations industrielles / Industrial Relations, 1955)
The article reviews the booklet, "Union Activity and Dual Loyalty," by Lois R. Dean. Reprint Series no. 23, New York State School of Industrial and Labor Relations at Cornell University, pp. 526-536.